Estrutura das interações abelhas-plantas: uso de plantas-iscas e análises polínicas para a determinação do nicho alimentar e descrição das redes ecológicas em sistemas naturais e cultivados - Rabelo, Laíce Souza (2016)
The food niche and the interactions between different groups of bees and plants can be studied, in dissimilar systems, using the association of tools, such as plant-bait, pollen analysis and interaction network approach. In this context, the general aim of this work was to study the interactions between bees and plants in two ecological systems: one natural, using species of Malpighiaceae as plant-baits, and other crop area, using the consortium between eggplant (Solanum melongena) and pumpkin (Cucurbita moschata) as bait plants. In the natural system, observations of the foraging behaviour and the analysis of pollen loads of oil-collecting bees sampled in Byrsonima spp. showed that: 1) the behaviour of foraging for pollen and oil was significantly associated with the taxonomic groups; 2) the main pollen source for these bees was Byrsonima spp. and 3) the robustness of interaction networks was influenced by the removal of bees according to the abundance, body size and taxonomic groups. Additionally, in this system we also studied the food niche of Exomalopsis fulvofasciata. This species foraged in five floral sources (being Byrsonima the most important) and used predominantly small pollen grains and flowers with non poricidal anthers. In the agrosystem, we observed a low similarity in the communities of flower visitors between the two crops that have been exploited for the collection of complementary resources (pollen and nectar). Furthermore, we observed that the complete system, formed by all bee species, both crops and surrounding plants, showed a greater robustness to the removal of species than all the simplest scenarios, except for the exclusion of bees according to their abundance. Thus, the results obtained in this study contributed to a greater understanding of bees-plants interactions in natural areas in Cerrado and crop areas. Information about the foraging behaviour and food niche, associated with simulations of possible extinction scenarios can be used to support actions of conservation and management of pollinators.